2019
DOI: 10.1016/j.ejvssr.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Presentation of Metastatic Renal Cell Carcinoma as an Arteriovenous Malformation Mimicking Vascular Tumour of the Forearm

Abstract: Introduction The development of metastatic renal cell carcinoma (RCC) many years after a nephrectomy is not common but has been reported. A metastasis appearing as a hypervascular tumour, mimicking an arteriovenous malformation (AVM), is a highly unusual phenomenon, with a biopsy required for diagnostic confirmation. Surgery is an option for a solitary metastatic lesion amenable to complete excision, with proven survival benefits. However, widespread metastatic disease carries a very poor prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As in our case, a hypervascular tumour was well demonstrated on conventional angiogram in which due to its hypervascularity, histopathological sampling was challenging. In another case, as reported by certain writers, RCC can metastasis in the form of an arteriovenous malformation, as Caunter G et al discovered (10). As a result, a hypervascular tumour is unlikely to be metastatic in origin.…”
Section: Discussionmentioning
confidence: 82%
“…As in our case, a hypervascular tumour was well demonstrated on conventional angiogram in which due to its hypervascularity, histopathological sampling was challenging. In another case, as reported by certain writers, RCC can metastasis in the form of an arteriovenous malformation, as Caunter G et al discovered (10). As a result, a hypervascular tumour is unlikely to be metastatic in origin.…”
Section: Discussionmentioning
confidence: 82%
“…The SMM from RCC occurs in <1% of patients and is described only in case reports ( 9 ). The reported reasons for the rarity of SMM from RCC can be summarized as the high vascularization of muscles; the lactic acid production in skeletal muscle may lead to angiogenesis resistance ( 46 , 47 ); high concentrations of free radicals, local temperature fluctuations, skeletal muscle-derived peptide factor, protease inhibitors, lymphocytes, and natural killers may inhibit metastasis ( 12 , 48 – 50 ); specific receptors which affect the metastasis potential of RCC may be missing or scarce in muscles ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of untreated patients with metastatic RCC was 6–12 months, and the 5-year survival rate was <20% ( 58 ). But for local metastases, surgical resection is beneficial to prolong survival ( 9 ) and five-year survival rates are between 35 and 50% after surgical therapy for solitary metastasis ( 17 , 59 ). Besides, it was also reported that in patients with multiple and non-lung-only metastasis, complete metastasectomy can bring the benefit of a 5-year survival rate to 32.5 vs. 12.4% without complete resection ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using computed tomography, a 2010 study detected SKM metastases in just 61/5170 (1.2%) patients with metastasized cancer [20]; metastases were most commonly associated with primary tumors of the genitals (24.6%), gastrointestinal tract (21.3%), urinary system (16.4%), and melanocytes (13.1%). Another study reported SKM metastasis occurred in <1% of patients with kidney cancer [21]. In addition, a 2012 study [5] confirmed the rarity of SKM metastases in patients with lung cancer (1.6%), with most metastases occurring in trunk muscles, suggesting that SKM metastases likely arise from adjacent tumors.…”
Section: Introductionmentioning
confidence: 96%